Peran Layanan Bimbingan dan Konseling dalam Mengatasi Kecanduan Media Sosial pada Siswa yang Berprestasi Rendah - Erma Erma; Agustina Malan; Ardwinner Joy Tumonglo (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This is a worrying issue in the digital age and has been shown to significantly contribute to low student academic achievement. This research aims to examine the role of Guidance and Counseling (BK) services in addressing social media addiction in students with low academic achievement. The method used in this research is library research with a qualitative approach through content analysis and literature synthesis techniques sourced from various scientific references published between 2020 and 2025. The results show that students addicted to social media have low self-control, resulting in academic procrastination and a consistent decline in learning achievement. GC services have proven to play a strategic role through preventive, curative, and developmental functions implemented through classical guidance, individual counseling, and group counseling. The Cognitive Behavioral Therapy (CBT) approach and self-management technique have proven most effective in helping students reduce social media addiction and improve learning discipline. However, the effectiveness of GC services is still constrained by the non-ideal ratio of counseling teachers, the lack of digital literacy-based GC programs, and students' negative stigma toward counseling services. This study recommends developing GC programs specifically designed to address digital addiction by involving the entire school ecosystem consistently.